From Classical Jurisprudence to Modern Practice: Forms of Named Contracts in Islamic Financial Institutions - Bagas Gumintang; Filda Khoirun Nikmah (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
Islam, as a comprehensive religion, is founded on universal values that guide both spiritual and social dimensions of human life. As social beings, humans depend on one another to meet diverse needs that cannot be fulfilled individually. Such interactions necessitate legal frameworks to regulate relationships, particularly through contracts that ensure stability and compliance with sharia principles. The concept of ijab-qabul serves as a symbol of mutual consent between contracting parties, reflecting the voluntary agreement essential in upholding the validity of contracts. This study employs a literature review with a descriptive-analytical approach, drawing primarily on data from Islamic financial institutions. It examines various forms of named contracts and their practical implementation within these institutions. The discussion highlights that understanding the legal implications of these contracts is a fundamental requirement for parties engaging in muamalah activities.